2021
DOI: 10.1016/j.envint.2021.106540
|View full text |Cite
|
Sign up to set email alerts
|

Changes in drug use in European cities during early COVID-19 lockdowns – A snapshot from wastewater analysis

Abstract: The COVID-19 outbreak has forced countries to introduce severe restrictive measures to contain its spread. In particular, physical distancing and restriction of movement have important consequences on human behaviour and potentially also on illicit drug use and supply. These changes can be associated with additional risks for users due to reduced supplies, limited prevention and harm reduction activities. Furthermore, there have been limitations in the amount of data about drug use which can be collected due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 10 publications
2
44
0
Order By: Relevance
“…Substance use was estimated as usual by most, trending toward a decrease. Similar findings were seen in online surveys among substance users in Switzerland [ 23 ], Europe [ 24 ], and Canada [ 25 ], or in wastewater analyses in European cities [ 26 ]. In those countries, decreases were more frequent for stimulants (e.g., cocaine, MDMA), mainly due to the closure of the night scene.…”
Section: Discussionsupporting
confidence: 81%
“…Substance use was estimated as usual by most, trending toward a decrease. Similar findings were seen in online surveys among substance users in Switzerland [ 23 ], Europe [ 24 ], and Canada [ 25 ], or in wastewater analyses in European cities [ 26 ]. In those countries, decreases were more frequent for stimulants (e.g., cocaine, MDMA), mainly due to the closure of the night scene.…”
Section: Discussionsupporting
confidence: 81%
“…One focused on one city in Austria, 6 while another covered eight cities in Europe, albeit for only 1 week during the pandemic. 7 These papers showed that the use of the more popular drugs such as cocaine, amphetamine, and MDMA generally decreased in most cities. In the Austrian study, the use of the traditionally less popular methamphetamine increased during lockdown conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this inconclusive evidence relating to whether drug use has increased or decreased has subsequently been supported in a trans-European study (seven countries) using wastewater analysis to examine the impact of 'stay at home orders' measures on specific stimulant and cannabis use. This study found that the picture was heterogenous rather than uniform indicating that potential responses to changes in drug use patterns are therefore hard to predict [85].…”
Section: Drug Use Patternsmentioning
confidence: 78%